2017
DOI: 10.1002/wene.245
|View full text |Cite
|
Sign up to set email alerts
|

Advanced biofuels production by upgrading of pyrolysis bio‐oil

Abstract: The present work is a review on the production of bio‐oils from biomass pyrolysis, with special emphasis on the different catalytic methods developed so far for the upgrading of this liquid fraction in order to significantly improve its properties, so it can be used as advanced biofuel. After a discussion of the main variables and factors affecting biomass pyrolysis, a number of processes are described here for bio‐oil upgrading, including catalytic pyrolysis, esterification, aldol condensation, ketonization, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 118 publications
0
55
0
1
Order By: Relevance
“…For 50,000 barrels per stream day FCC unit and 2.25 vol% bio‐oil addition, the process benefits were calculated at $13–26 and at $47–60 per barrel of bio‐oil for renewable identification number (RIN) prices of $1.64/RIN and $2.55/RIN, respectively. Talmadge et al () carried out a techno‐economic analysis for the co‐processing of raw bio‐oil with VGO using data from the Petrobras demonstration plant runs (Almeida & Pinho, ; de Rezende Pinho et al, , , ). Their study suggested that co‐processing up to 5 wt% of bio‐oil would be economically feasible in the near‐term, assuming a 400 dry tonnes/day biomass pyrolysis plant and a bio‐oil cost of $80–84/bbl.…”
Section: Economic Feasibility Of Fcc Co‐processing In the Refinerymentioning
confidence: 99%
See 1 more Smart Citation
“…For 50,000 barrels per stream day FCC unit and 2.25 vol% bio‐oil addition, the process benefits were calculated at $13–26 and at $47–60 per barrel of bio‐oil for renewable identification number (RIN) prices of $1.64/RIN and $2.55/RIN, respectively. Talmadge et al () carried out a techno‐economic analysis for the co‐processing of raw bio‐oil with VGO using data from the Petrobras demonstration plant runs (Almeida & Pinho, ; de Rezende Pinho et al, , , ). Their study suggested that co‐processing up to 5 wt% of bio‐oil would be economically feasible in the near‐term, assuming a 400 dry tonnes/day biomass pyrolysis plant and a bio‐oil cost of $80–84/bbl.…”
Section: Economic Feasibility Of Fcc Co‐processing In the Refinerymentioning
confidence: 99%
“…Alternatively, raw bio‐oil can be almost completely deoxygenated and converted into a mixture of liquid hydrocarbons via hydrodeoxygenation (Elliott, ). Hydrodeoxygenation is carried out at intermediate temperature (200–350°C, Fermoso, Pizarro, Coronado, & Serrano, ), high pressure (50–150 bar, Fermoso et al, ) and under hydrogen atmosphere in the presence of a heterogeneous hydrogenation catalyst (Bridgwater, ). Due to the instability of raw bio‐oil and in order to ensure continuous processing, complete hydrodeoxygenation needs to be carried out in multiple steps (Elliott, ), which adds to the complexity of the process.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of its renewable nature, the low content of S and N, and neutral CO 2 balance for combustion, bio-oil is not suitable for direct use as a fuel due to its instability and properties (such as high water and oxygen content, acidity, corrosiveness and low viscosity). Consequently, several processes have been proposed for stabilizing, conditioning and up-grading bio-oil in order to convert it into platform chemicals (olefins and BTX), liquid fuels or H 2 [10][11][12]. Thus, the bio-oil produced in decentralised pyrolysis units can be subsequently transported to a centralized unit for H 2 production.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, certain oxygenated components (particularly the phenolic compounds) polymerize during the bio‐oil vaporization, which is a necessary step for bio‐oil valorization through catalytic processes. Consequently, several methods for stabilizing and/or conditioning the raw bio‐oil have been proposed in the literature with the aim of facilitating its valorization into fuels and raw chemicals …”
Section: Production and Characteristics Of Bio‐oilmentioning
confidence: 99%